Isolation of Salmonella from tissue and environmental samples and assessment of risk factors in commercial layers in Argentina - Soria, Mario; Godano, Eduardo Ignacio; Leiva, Leonardo Esteban; Shehata, Awad A.; Bueno, Dante Javier (German Multidisciplinary Publishing Center (GMPC), 2025)
This study aimed to evaluate the isolation methods of Salmonella from tissues and environmental samples collected during natural Salmonella outbreaks in commercial layer farms in Argentina. We also assessed key risk factors for contamination with Salmonella serovar Gallinarum biovar Gallinarum (SG) in poultry houses. To achieve this, we collected tissue samples from 20 houses (n=398; including spleen, liver, ovary, cecal contents, and bone marrow) and environmental samples (n=510; including feed, eggs, feces, and water) from deceased laying hens and their surroundings. Various isolation procedures were employed using different media. Salmonella was identified based on biochemical tests and serotyping using agglutination tests. Results showed that out of 398 tissue samples, 247 (62%) were positive for SG: bone marrow (62/80), spleen (59/79), liver (57/80), ovary (51/80), and cecum 18/79). Salmonella spp. was detected in 25% (1/4), 17% (2/12), 10.6% (10/94), and 3.6% (4/110) in boot swabs, egg nests, feces, and feed, respectively. Additionally, samples of yolk egg pool (1/74) and eggshell pool (1/74) were positive for SG. Among isolated serovars, S. ser. Cerro was the most frequently isolated serovar, followed by SG, S. ser. Livingstone, S. ser. Enteritidis, S. ser. Derby, S. ser. Corvallis, S. ser. Infantis, S. ser. Mbandaka, S. ser. Montevideo, S. ser. Schwarzengrund, and S. ser. Heidelberg, which were all isolated from environmental samples. Notably, four poultry houses exhibited contamination with multiple serotypes, with three or four serotypes present. Multiple logistic regression analyses revealed that vaccination against SG and effective insect control notably decreased the spread of Salmonella on poultry farms. Our results emphasize the importance of using diverse sample types and detection techniques for isolating and identifying Salmonella. This data could also contribute to developing improved control programs and intervention strategies at the farm level to minimize Salmonella contamination in poultry.